Uma abordagem heurística para o problema de roteamento DIAL-A-RIDE. - Costa, Daniel Leite Viana (2013)
Problems of traffic jam, lack of vacancies in garages and cars underutilized are part of the current scenario of big cities. In this work is created a module for creating efficient routes for a system using the approach Dial-a-Ride Problem. The DARP is a vehicle routing problem that belongs to NP-complete class. It aims is to minimize operating costs while maintaining quality of service to the client. It is presented an algorithm that uses the metaheuristics Iterated Local Search with the Variable Neighborhood Search to solve the DARP. Compared to related work in the area, the results were better regarding to distance traveled and average travel time of customers.